The association between different traumatic life events and suicidality - Ásgeirsdóttir, Hildur G. (Eur J Psychotraumatol, 2018)
Background: Traumatic life events have been associated with increased risk of various psychiatric disorders, even suicidality. Our aim was to investigate the association between different traumatic life events and suicidality, by type of event and gender. Methods: Women attending a cancer screening programme in Iceland (n = 689) and a random sample of men from the general population (n = 709) were invited to participate. In a web-based questionnaire, life events were assessed with the Life Stressor Checklist – Revised, and the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criterion was used to identify traumatic life events. Reports of lifetime suicidal thoughts, self-harm with suicidal intent and suicide attempt were considered as lifetime suicidality. We used Poisson regression, adjusted for demographic factors, to express relative risks (RRs) as a measure of the associations between traumatic events and suicidality. Results: Response rate was 66% (922/1398). The prevalence of lifetime traumatic events was 76% among women and 77% among men. Lifetime suicidality was 11% among women and 16% among men. An overall association of having experienced traumatic life events with suicidality was observed [RR 2.05, 95% confidence interval (CI) 1.21–3.75], with a stronger association for men (RR 3.14, 95% CI 1.25–7.89) than for women (RR 1.45, 95% CI 0.70–2.99). Increased likelihood for suicidality was observed among those who had experienced interpersonal trauma (RR 2.97, 95% CI 1.67–5.67), childhood trauma (RR 4.09, 95% CI 2.27–7.36) and sexual trauma (RR 3.44, 95% CI 1.85–6.37), with a higher likelihood for men. In addition, an association between non-interpersonal trauma and suicidality was noted among men (RR 3.27, 95% CI 1.30–8.25) but not women (RR 1.27, 95% CI 0.59–2.70). Conclusion: Findings indicate that traumatic life events are associated with suicidality, especially among men, with the strongest association for interpersonal trauma.